La transparence et l’obstacle. Analytique du contrôle aux checkpoints dans l’Irak post-Saddam - Juliette Duclos-Valois (Les Cahiers d’EMAM)
From 2003 onwards, checkpoints appeared all across Iraq. These spaces serve as instruments of territorialization for various competing powers in the country. As internal boundaries, they constitute obligatory passage points for residents, complicating daily life and subjecting people and their movements to constant scrutiny. Supposedly designed to secure areas, checkpoints and their surroundings have become danger zones where different antagonisms are expressed. Depending on the checkpoint and background of the individual, security forces profile and label people. Individuals are then subjected to various forms of violence based on these perceptions of ethno-sectarian identity and the discrimination they incur. This article explores the widening gap between the official function of checkpoints and their operational reality. It reveals the interplay of indexical strategies that underpin both the control mechanisms and the individual efforts made to thwart them. In doing so, it delineates the weight of this security apparatus on the life and aspirations of individuals in Iraq.